The Effect of Audit Fees, Audit Tenure, and Leverage Ongoing Concerns Audit Opinion - Depari, Cynthia Veronika; Wulandari, Putu Prima (Basic and Applied Accounting Research Journal, 2024)
This research aims to determine the empirical evidence of the effect of audit fees and audit tenure and leverage ongoing concerns of audit opinion. This research uses secondary data in the form of annual financial reports of retail trade companies for 2020-2022. The population used in this research is retail trade companies listed on the Indonesia Stock Exchange (IDX) for 2020-2022. The samples in this research were selected using a purposive sampling method. The number of companies sampled in the study is 23 retail trade companies over 3 years, and the total research samples are 69. The data was analyzed using logistic regression and processed using SPSS version 25. This research suggests that audit tenure harms going concern audit opinion as the length of the agreement between the auditor and the client can affect the going concern audit opinion. Audit fees and leverage do not affect going-concern audit opinions because other factors may affect them.